IOT BASED HYDROPONIC WATER QUALITY CONTROL INTEGRATED WITH WEBSITE AND EARLY WARNING - Herman Saputra; Nofriadi Nofriadi (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2026)
Abstract: The development of information and communication technology has driven digital transformation in various sectors, including agriculture. One of the technologies widely applied is the Internet of Things (IoT), which enables devices to be interconnected through the internet to perform monitoring and data exchange in real time. In hydroponic cultivation, water quality stability is a crucial factor that affects plant growth. The main parameters that need to be monitored include water acidity level (pH), water temperature, and dissolved nutrient concentration measured using Total Dissolved Solids (TDS). However, water quality monitoring is still commonly conducted manually, making it less efficient and potentially causing delays in detecting changes in water conditions. This study aims to design an IoT-based water quality monitoring system for hydroponic cultivation using an ESP32 microcontroller integrated with pH, temperature, and TDS sensors. The collected data are sent to a server and displayed on a web dashboard in real time, equipped with automatic notification features. The proposed system is expected to improve monitoring efficiency and increase the productivity of hydroponic cultivation Keywords: esp32; hydroponics; internet of things; real-time monitoring; water quality. Abstrak: Perkembangan teknologi informasi dan komunikasi mendorong transformasi digital dalam berbagai sektor, termasuk pertanian. Salah satu teknologi yang banyak diterapkan adalah Internet of Things (IoT) yang memungkinkan perangkat saling terhubung melalui jaringan internet untuk melakukan pemantauan dan pertukaran data secara real-time. Pada budidaya hidroponik, kestabilan kualitas air menjadi faktor penting yang mempengaruhi pertumbuhan tanaman. Parameter utama yang perlu diperhatikan meliputi tingkat keasaman air (pH), suhu air, serta konsentrasi nutrisi terlarut yang diukur menggunakan Total Dissolved Solids (TDS). Namun, pemantauan kualitas air masih banyak dilakukan secara manual sehingga kurang efisien dan berpotensi menimbulkan keterlambatan dalam mendeteksi perubahan kondisi air. Penelitian ini bertujuan merancang sistem pemantauan kualitas air hidroponik berbasis IoT menggunakan mikrokontroler ESP32 yang terintegrasi dengan sensor pH, suhu, dan TDS. Data dikirim ke server dan ditampilkan pada web dashboard secara real-time serta dilengkapi notifikasi otomatis. Sistem ini diharapkan meningkatkan efisiensi pemantauan dan produktivitas budidaya hidroponik. Kata kunci: esp32; hidroponik; internet of things; kualitas air; monitoring real-time